Optimalisasi Peran Pecalang Segara dalam Melakukan Pengawasan Aktivitas Melaut yang Berdampak pada Rusaknya Ekosistem Terumbu Karang di Desa Adat Pemuteran Bali Utara - I Gede Yoga Esa Mahendra; I Wayan Landrawan; Ni Ketut Sari Adnyani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the role and optimization strategies of Pecalang Segara in monitoring fishing activities that contribute to coral reef ecosystem degradation in the Traditional Village of Pemuteran, North Bali. Pecalang Segara is a customary security institution that holds social legitimacy and customary authority in maintaining order within coastal areas. This research applies an empirical legal approach using a qualitative descriptive method. Data were collected through field observations, interviews with customary leaders and coastal communities, and a literature review of environmental laws and related regulations. The findings indicate that Pecalang Segara plays a strategic role in supervising fishing activities based on local wisdom, particularly in preventing destructive fishing practices that damage coral reefs. However, the effectiveness of this role remains limited due to insufficient technical capacity, low environmental legal awareness, and weak integration between customary law and formal legal systems. The study highlights the importance of strengthening Pecalang Segara through environmental education, regulatory-based monitoring training, and institutional coordination with local government authorities. The integration of customary law and national environmental law is expected to establish a sustainable community-based marine monitoring model capable of effectively protecting coral reef ecosystems and supporting environmental governance in coastal areas.